Effects of training frequency during a 6-month neuromuscular training intervention on movement competency, strength, and power in male youth - Lloyd, R. S.; Dobbs, I. J.; Wong, M. A.; Moore, I. S.; Oliver, J. L. (Sports Health: A Multidisciplinary Approach, 2022)
Background: Youth populations benefit from neuromuscular training; however, the extent to which training frequency, baseline fitness, and maturity status moderate the response to long-term neuromuscular training in male youth remains unclear. Hypothesis: Twice-weekly training (G2x) would induce larger improvements in movement competency and strength and power kinetics compared with once-weekly training (G1x). Maturity status and baseline fitness would also moderate the training response in strength and power kinetics. Study Design: Nonrandomized, repeated-measures design. Level of Evidence: Level 3 Methods: Ninety-five male athletes of varying maturity status (pre- or post-peak height velocity) were divided into G2x, G1x, or control (CON) groups. Training groups received G2x or G1x for 28 weeks. Back squat assessment (BSA) movement competency and isometric mid-thigh pull (IMTP), squat jump (SJ), and countermovement jump (CMJ) kinetics were measured pre- and postintervention. Results: The G2x achieved significantly greater adaptations in BSA total score, IMTP allometrically scaled peak force (PFallo), IMTP peak rate-of-force development (PRFD), SJ PFallo and PRFD compared with G1x and CON (P < 0.05; d = 0.3-0.9). Baseline fitness, training frequency and maturity status were significant predictors of IMTP PFallo (R2 = 27.5%) and PRFD (R2 = 42.9%), while a combination of training frequency and baseline fitness explained a small amount of variance in SJ PFallo (R2 = 12.2%) and SJ PRFD (R2 = 6.5%). There were no significant predictors of CMJ kinetics. Conclusion: G2x achieved significantly larger improvements in movement competency, isometric strength and concentric jump variables compared with G1x, with the training response greater in those youth with lower baseline fitness and more advanced maturity status. Clinical Relevance: Exposure to neuromuscular training twice-weekly elicits a greater response than G1x in young male athletes. Practitioners should take maturity status, training frequency, and baseline fitness levels of young male athletes into account when interpreting testing data, as these variables appear to moderate training responsiveness.